Multiple Mixing Ratios of Gamma Rays - Younis, T. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The ï¤-mixing of ï§ - transition in Er 168 populated in  Er(n,n ) Er 168 168 ï‚¢ï§ reaction is calculated in the present work by using a2- ratio method. This method has used in previou studies [4, 5, 6, 7] in case that the second transition is pure or for that transition which can be considered as pure only, but in one work we applied this method for two cases, in the first one for pure transition and in the 2nd one for non pure transitions. We take into accunt the experimental a2- coefficient for previous works and ï¤-values for one transition only [1]. The results obtained are, in general, in agood agreement within associated errors, with those reported previously [1], the discrepancies that occur are due to inaccuracies existing in the experimental data of the previous works.